Inverse Network DEA Incorporating Cost and Revenue Efficiencies Under Fuzzy Uncertainty - Fatemeh Gholami Golsefid; Monireh Jahani Sayyad Noveiri; Sohrab Kordrostami (Journal of Mathematics)
The study of network cost and revenue efficiency and changes related to performance measures in uncertain environments is an important area of research in decision-making analysis. A generalized inverse data envelopment analysis (DEA) approach is advanced in this examination for addressing the complexities associated with imprecise inputs and outputs within two-stage networks. Additionally, the second stage of the network is evaluated for the existence of unwanted outputs. The proposed methodology focuses on estimating fuzzy performance measures in two-stage processes while maintaining consistent fuzzy technical efficiency and cost efficiency (revenue efficiency). To demonstrate the practical application of this approach, data from various branches of a bank in Iran, which are characterized by inaccurate data and undesirable outputs, is analyzed, yielding logical and insightful results.